Sulodexide Significantly Improves Endothelial Dysfunction and Alleviates Chest Pain and Palpitations in Patients With Long-COVID-19: Insights From TUN-EndCOV Study - Charfeddine, Salma; Ibnhadjamor, Hassen; Jdidi, Jihen; Torjmen, Slim; Kraiem, Salma; Bahloul, Amine; Makni, Ahmed; Kallel, Nesrine; Moussa, Nedia; Boudaya, Mariem; Touil, Imen; Ghrab, Aiman; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective Non-respiratory long-coronavirus disease 2019 (COVID-19) symptoms are mainly related to a long-lasting endothelial dysfunction and microcirculation impairment. We hypothesized that Sulodexide, a purified glycosaminoglycan mixture with a beneficial endothelial effect in arterial and venous peripheral diseases, may be effective in a subset of patients with long COVID-19. Approach and Results We conducted a multicenter prospective quasi-experimental study. A total of 290 patients from the TUN-EndCOV study with long-COVID-19 symptoms and endothelial dysfunction were included. The endothelial function was clinically assessed using a post-occlusive reactive hyperemia protocol with finger thermal monitoring device. Endothelial quality index (EQI) was assessed at inclusion and at 21 days later. The study population was assigned to a sulodexide group (144 patients) or a no-medical treatment group (146 patients). Clinical characteristics were similar at inclusion in the two groups. Fatigue, shortness of breath, and chest pain were the most common symptoms, respectively, 54.5, 53.8, and 28.3%. At 21 days, the sulodexide group improved significantly better than the no-medical treatment group in chest pain (83.7 vs. 43.6%, p < 10−3), palpitations (85.2 vs. 52.9%, p = 0.009), and endothelial function [median delta-EQI 0.66 (0.6) vs. 0.18 (0.3); p < 10−3]. Endothelial function improvement was significantly correlated with chest pain and palpitations recovery (AUC, i.e., area under the curve = 0.66, CI [0.57– 0.75], p = 0.001 and AUC = 0.60, CI [0.51– 0.69], p = 0.03, respectively). Conclusion Sulodexide significantly improves long-lasting post-COVID-19 endothelial dysfunction and alleviates chest pain and palpitations.